2015
DOI: 10.3748/wjg.v21.i3.913
|View full text |Cite
|
Sign up to set email alerts
|

Association of nonalcoholic fatty liver disease and liver cancer

Abstract: NAFLD is more common in patients with liver metastases caused by colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Today, NAFLD is becoming the leading cause of chronic liver disease, afflicting 25% of adults in the United States. Although liver metastasis can occur in CRC patients without NAFLD, a recent large prospective human cohort analyzing 2,715 CRC patients with liver metastasis as well as other retrospective studies have suggested that the patients with NAFLD have an increased risk of liver metastasis and for the recurrence of liver metastasis after resection, when compared with patients without NAFLD . Moreover, higher recurrence rate of liver metastasis in patients with fibrosis have also been reported in recent studies .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Today, NAFLD is becoming the leading cause of chronic liver disease, afflicting 25% of adults in the United States. Although liver metastasis can occur in CRC patients without NAFLD, a recent large prospective human cohort analyzing 2,715 CRC patients with liver metastasis as well as other retrospective studies have suggested that the patients with NAFLD have an increased risk of liver metastasis and for the recurrence of liver metastasis after resection, when compared with patients without NAFLD . Moreover, higher recurrence rate of liver metastasis in patients with fibrosis have also been reported in recent studies .…”
Section: Discussionmentioning
confidence: 89%
“…Previous animal studies have demonstrated that high‐fat diet (HFD)‐induced NAFLD promotes the tumor growth of CRC and PDAC liver metastasis . Large prospective and retrospective human cohorts have demonstrated that cancer patients with NAFLD have increased risk of liver metastasis and for recurrence after resection of liver metastasis compared with patients without NAFLD . The increased prevalence of obesity and NAFLD will likely increase the occurrence of liver metastasis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The application of such patches during the surgical intervention could allow avoiding intraportal MSC injection that may cause embolization and be lethal for patients who have undergone massive hepatectomy. Moreover, there is an emerging evidence of hepatocellular carcinoma in noncirrhotic NAFLD and NAFLD prevalence in patients with hepatic metastases from colorectal cancer is high (Schulz et al, ). Therefore, the number of patients requiring liver surgery is increasing in parallel with NAFDL.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular deposition of lipid leads to oxidative stress in hepatocytes and also induces cytokine‐mediated injury (Parola & Robino, ). An elevated level of cytokines and macrophages in systemic circulation remodels the extracellular matrix and leads to a more lethal condition like inflammation, fibrosis, and HCC (Decaris et al, ; Schulz et al, ).…”
Section: Introductionmentioning
confidence: 99%